PEMBINAAN KEDISIPLINAN SISWA MELALUI BIMBINGAN DAN ETIKA DI MADRASAH TSANAWIYAH NEGERI 2 KOTA JAMBI - Salwa, Saidah; Fransisko Chaniago; Djuwairiah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the cultivation of student discipline through guidance and ethics at Madrasah Tsanawiyah Negeri 2 Kota Jambi. The research employed a qualitative approach with a case study design, collecting data through observations, interviews, and documentation. The findings indicate that fostering student discipline through punctuality, systematic supervision, persuasive motivation, and the ethical implementation of rewards and punishments is effective in shaping positive and sustainable behavior. This approach not only emphasizes formal compliance with rules but also nurtures students’ internal awareness of personal responsibility and ethical values. The combination of pedagogical strategies, a humanistic approach, and the integration of ethical principles promotes active student engagement, adherence to school regulations, and the internalization of discipline as part of the school culture, thereby supporting the comprehensive and sustainable development of student character.